(De)colonising outcomes of community participation – a South African ethnography of ‘ethics in practice’ - Brear, Michelle R.; Tsotetsi, Cias T. (SAGE Publications, 2022)
Theoretically, community participation decolonises research ethics in settings where a ‘coloniality of power’ persists. We used ethnographic methods to document our experiences of ‘ethics in practice’, and interrogate the (de)colonising outcomes, of community participation in voluntary informed assent and consent (VIAC) procedures with 16–17-year-old Black South African youth and parents. Community participation decolonised by: (1) disrupting and problematising the power dynamics of written VIAC procedures and (2) minimally shifting power to youth and parents. However, community participation sometimes reinforced existing power hierarchies. In postcolonial qualitative research settings, community participation has potential to, but will not necessarily, decolonise ethics in practice.
Keywords: Transdisciplinary approaches; Community participation; Power; Decolonisation; Voluntary informed consent; Research ethics